Cuidados de enfermería en pacientes con catéter venoso central en la unidad de cuidados intensivos - Mora Chiles, Johanna Germania (2025)
Background: Nursing knowledge about the care of the central venous catheter (CVC) is essential in the management of critical patients, especially when the peripheral pathways are not adequate since its use allows the administration of complex treatments and safer monitoring. The need for and importance of nursing staff to be highly trained, updated in procedures for inserting and maintaining CVC care, to prevent long-term complications, was emphasized. Objective: To identify nursing care in patients with central venous catheter in the Intensive Care Unit. Method: A qualitative research was used, which is supported by the literature review of journal articles, master's theses, books, doctorates, which provided information related to nursing care in patients with central venous catheter in the Intensive Care Unit. Results: The analysis of the literature review showed that nursing staff must know and rigorously apply the established protocols, since their continuous surveillance helps in the early detection of risks, in addition, a significant problem related to infections associated with the inadequate handling of the CVC was identified, likewise, criteria were compared based on the reduction of infections through the appropriate use of antiseptics and how the saline solution is an alternative to heparin with respect to the permeabilization of lumens. Conclusions: These results highlight the need for continuous surveillance and the updating of fundamental techniques to optimize care and minimize risks.